Electron-hole interactions and metal-insulator transitions in InAs/GaSb heterostructures - Nicholas, R; Takashima, K; Kardynal, B; Petchsingh, C; Mason, N; Maude, D; Portal, J; IPAP; IPAP (2001)
InAs/GaSb heterojunctions form bipolar 2-D layers due to the overlapping conduction and valence bands. Such systems have generated considerable interest recently due to the possibilities of gap formation by both excitonic and single particle interactions. The quantum Hall effect in this system shows a digital sequence oscillating from 0-1-0 conductance quanta and the diagonal resistivity, p. shows re-entrant insulating behaviour due to the formation of a total gap in the energy spectrum. The origin of the insulating behaviour is thought to be due to the formation of unusual counter propagating edge states where the electron and hole system interact to form closed loops which generate localised states. Cyclotron resonance on this system is found to show an increased effective mass when the electron and hole states approach each other physically and at high magnetic fields the resonances show large splittings which can be strongly temperature dependent.